Taxing Multinationals in Europe - Crivelli, Ernesto; De Vrijer, J. E. J.; Hebous, Shafik; Mooij, Ruud A. (Washington, D.C. : International Monetary Fund, 2021)
This paper aims to contribute to the European policy debate on corporate income tax reform in three ways. First, it takes a step back to review the performance of the CIT in Europe over the past several decades and the important role played by MNEs in European economies. Second, it analyses corporate tax spillovers in Europe with a focus on the channels and magnitudes of both profit shifting and CIT competition. Third, the paper examines the progress made in European CIT coordination and discusses reforms to strengthen the harmonization of corporate tax policies, in order to effectively reduce both tax competition and profit shifting.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Corporate Finance and Governance; Economywide Country Studies